2023
DOI: 10.13057/asianjfor/r070205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plant diversity between managed and unmanaged forests in Haftkhal, Mazandaran Province, North of Iran

SHIRZAD MOHAMMADNEZHAD-KIASARI,
KHOSRO SAGHEB-TALEBI,
RAMIN RAHMANI
et al.

Abstract: Abstract. Kiasari MSh, Sagheb-Talebi Kh, Rahmani R, Ghelichnia H. 2023. Comparison of plant diversity between managed and unmanaged forests in Haftkhal, Mazandaran Province, North of Iran. Asian J For 7: 106-113. The relationship of plant diversity with silvicultural practices has not been fully understood for the oriental beech forests (Fagus orientalis Lipsky), which is a widespread forest tree in the Hyrcanian Region, Iran. The implementation of appropriate forestry practices in the oriental beech forests i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In our study, the Simpson Diversity Index was found to be slightly low (0.61) in the conventionally managed forest blocks than that (0.67) in the sustainably managed ones, which indicated that the conventionally managed forest blocks had higher plant diversity as compared to that in the sustainably managed ones; these results were similar to those obtained by Monarrez-Gonzalez et al (2020) in Mexico. Likewise, the lower value of the Species Evenness Index (0.82) in the sustainably managed forest blocks as compared to that (0.88) in the unmanaged ones also supported the results, which were similar to those obtained by Mohammadnezhad-Kiasari et al (2023).…”
Section: Discussionsupporting
confidence: 85%
“…In our study, the Simpson Diversity Index was found to be slightly low (0.61) in the conventionally managed forest blocks than that (0.67) in the sustainably managed ones, which indicated that the conventionally managed forest blocks had higher plant diversity as compared to that in the sustainably managed ones; these results were similar to those obtained by Monarrez-Gonzalez et al (2020) in Mexico. Likewise, the lower value of the Species Evenness Index (0.82) in the sustainably managed forest blocks as compared to that (0.88) in the unmanaged ones also supported the results, which were similar to those obtained by Mohammadnezhad-Kiasari et al (2023).…”
Section: Discussionsupporting
confidence: 85%